Phytochemical-based nanodrugs going beyond the state-of-the-art in cancer management—Targeting cancer stem cells in the framework of predictive, preventive, personalized medicine - Koklesova, Lenka; Jakubikova, Jana; Cholujova, Dana; Samec, Marek; Mazurakova, Alena; Šudomová, Miroslava; Pec, Martin; Hassan, Sherif T. S.; Biringer, Kamil; Büsselberg, Dietrich; Hurtova, Tatiana; Golubnitschaja, Olga; et al. (Frontiers in Pharmacology, 2023)
Nanotherapeutic agents have the potential to go beyond state-of-the-art approaches in overall cancer management. Specially assembled nanoparticles (NPs) act as carriers for targeted drug delivery. Several nanodrugs have already been approved by the US Food and Drug Administration (FDA) for treating different cancer types. However, targeted cancer stem cells (CSCs) treatment is still an issue in protecting affected individuals against associated multidrug resistance and disease progression. Corresponding conceptual innovation and technological solutions demand multi-professional expertise following principles of 3P medicine, namely predictive approaches, targeted prevention, and personalization of medical services in primary, secondary, and tertiary care. Phytochemicals isolated from plants demonstrate considerable potential for nanomedical applications in oncology thanks to their antioxidant, anti-inflammatory, anti-proliferative, and other health benefits. Phytochemical-based NPs can enhance anticancer therapeutic effects, improve cellular uptake of therapeutic agents, and mitigate the side effects of toxic anticancer treatments. Per evidence, phytochemical-based NPs can specifically target CSCs decreasing risks of tumor relapse and metastatic disease manifestation. A particular value of phytochemical-based anticancer effects is considered in the framework of predictive, preventive, and personalized medicine (3PM). The key points are the cost-efficacy of healthcare and the life quality of affected individuals. Targeted treatment needs to be adapted to the individualized patient profile in primary, secondary, and tertiary care.